Juvenile justice in the children’s rights ensuring system (Journal of actual problems of jurisprudence, 2019)
The relevance of this article is dictated by the fact that the child is one of the key figures of the legal society. The phenomenon of the rights of the child includes not only the naturally granted ability to have rights and freedoms, but also a formed system to ensure them, which contains a number of forms (social and legal institutions) designed to take into account the best interests of the minor and compensate for the disadvantages of his age status. Juvenile justice is one of the main forms of ensuring (protecting) the rights of children in a specific area of legal relations – justice and other related public relations. Considering the pluralism of juvenile justice concepts and the organizational and legal forms of its functioning in various countries, the goal (task) of this scientific research is to form a modern understanding of the praxeological dimension of juvenile justice in the system of ensuring the rights, freedoms and interests of children. The issue of juvenile justice format is particularly relevant for countries where this institution is at the stage of formation and testing, and the ideas of scientific research can be implemented into national legislation to improve the mechanisms for ensuring the rights of children. The methodological basis of the work consisted of a systematic approach, a method of abstraction, analysis, induction, comparison. In addition, special scientific research methods are widely used: the method of legal hermeneutics, comparative, logical-semantic, etc. For convenience of analysis, the article highlights two main approaches in understanding the essence and boundaries of juvenile justice: the view of juvenile justice solely as a specific form of justice for children; expanding the boundaries of this institution to include a number of related preventive, social, medico-psychological, penological and post-penological activities aimed at ensuring the best interests of the child in all these legal relationships. As a result of the study, it was established that juvenile justice is not only a different approach to a juvenile offender within criminal proceedings, but a social and legal institution that forms a specialized justice system for children and for children, as well as a set of mechanisms pedagogical and rehabilitation procedures and programs designed to ensure the rights, freedoms and legitimate interests of children in difficult life circumstances, implemented by the State and non-state bodies. Understanding of juvenile justice as an integrated systemic and multi-institutional type of activity transcending beyond the criminal justice process, determines the existence of a broad administrative and legal component in the functioning of this form of ensuring the rights of children.